Empowering the vulnerable sector through local planning the case of Gawad Kalinga housing project for persons with disabilities (PWDs) at Escopa III, Quezon City - Taluban, Joseph G. Jr.; Chaves, Carmeli Marie C.; Gomez, Jose Edgardo A. Jr.; Magnaye, Dina C. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2021)
This research correlates housing to the Socio-economic improvement of marginalized Persons with Disabilities (PWDs) and their resilience to flooding. The first part presents their predicaments and how shelter, being one of the basic needs, has been neglected in any PWD program-both national or local. Their right to proper housing, at par with others, is justified in the study framework. Empowerment enables them to become better in life and contribute to the growth of society. A well-planned PWD housing has been identified a tool to achieve these. This research occurred in the outbreak of COVID-19. We have witnessed how the poorest of the poor-including PWDs, have tremendously suffered during the lockdown and imposed community quarantine. Job loss loomed and they had no choice but to rely on various assistance. Aside from the pandemic, we recall how flash floods towards the end of 2020 affected urban and rural landscapes, damaging properties and leaving pointless deaths. This research gives a timely and relevant position on how to address the needs of PWDs in providing a long-term solution.
Thesis (M. A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Public housing -- Philippines -- Quezon City; People with disabilities -- Philippines -- Quezon City; Community development -- Philippines -- Quezon City; Escopa III, Quezon City -- Housing condition